2018
DOI: 10.3892/ol.2018.8821
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of icariin on osteosarcoma cell proliferation via the Wnt/β-catenin signaling pathway

Abstract: Osteosarcoma, is a kind of malignant tumor derived from malignant interstitial cells. The pathogenesis of osteosarcoma remains unclear and despite use of chemotherapy drugs, resistance to these drugs affects the success of treatment. The present study was conducted to investigate the effects of icariin (ICA) on osteosarcoma cell proliferation and to investigate the role of the Wnt/β-catenin signaling pathway in the inhibition process of ICA on osteosarcoma cell proliferation. Different concentrations of ICA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…In contrast, p21 expression level was increased with ICA treatment. These results were consistent with previous research, indicating that ICA may inhibit tumor cell proliferation (36). The findings of the present study indicated that ICA may have increased G 1 cell cycle arrest and inhibited DNA synthesis in SKOV3 cells.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast, p21 expression level was increased with ICA treatment. These results were consistent with previous research, indicating that ICA may inhibit tumor cell proliferation (36). The findings of the present study indicated that ICA may have increased G 1 cell cycle arrest and inhibited DNA synthesis in SKOV3 cells.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, Glycogen Synthase Kinase-3β (GSK-3β) is involved in cell cycle progression and proliferation of multiple tumors, including osteosarcoma [15]. The involvement of the β-catenin/cyclin D 1 pathway in cell proliferation and differentiation consider as a crucial signaling pathway [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have been directed toward the biochemical inhibition of cellular proliferation in PVR, but the effect is not ideal. ICA is a pharmacologically active flavonoid that can suppress growth and promote apoptosis in a variety of malignant cells (Sun et al, 2016b;Ren, Zhu & Liu, 2018). Additionally, ICA prevents against mitogen-induced aberrant proliferation in other cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, emerging studies have reported ICA regulates cell cycle progression and proliferation in various cell types. ICA exerted suppressive effects on medulloblastoma cells (Sun et al, 2016b), osteosarcoma cells (Ren, Zhu & Liu, 2018) and human aortic smooth muscle cells (HA-VSMCs) (Hu et al, 2016). Further, the induction of G0/G1 phase arrest was observed in cardiomyocyte and breast cancer cells after treatment with ICA (Zhu et al, 2005;Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%